(Un)stitching the Memory and the Story of a Melanoma: Giving a Form to Forgetfulness between Anthropology and Creative Ethnographic Drawing - Noronha, Susana de (2019)
The visual essay and triptych “Erase the past; It’s over; Move on” is the result of an anthropological analysis of the cancer experience of a Portuguese woman, “Violeta”, whose story is told by her daughter “Flor”, thirty years after her death. Blending embodied knowledge, oral narrative, anthropology and scientific illustration, enhanced by metaphor and imagination, the use of creative ethnographic drawing gives a shape to the undivided processes of memory and forgetfulness pervading this narrative. Using drawing as a methodological resource, this hybrid exercise involves a balanced mixture of speech, text, and image, grounded in the words of the interviewed woman. It suggests an ontological, epistemological and performative understanding of the artistic and visual practices of illustration, using them as extensions of knowledge and action, enlarging the way we can understand and act on the impacts of illness and death, and (un)making memory. “Flor” agreed to tell the story, but she does not want to remember the experience: her resistance strategy was based on forgetting and erasing the past. The set of three drawings conveys this difficult process of rebuilding one’s memory out of fragments, but also the will to lose it again, breaking the thread that unites them.